EMP3 sustains oncogenic EGFR/CDK2 signaling by restricting receptor degradation in glioblastoma - Martija, Antoni Andreu; Krauß, Alexandra; Bächle, Natalie; Doth, Laura; Christians, Arne; Krunic, Damir; Schneider, Martin; Helm, Dominic; Will, Rainer D.; Hartmann, Christian; Herold-Mende, Christel; Deimling, Andreas von; et al. (Acta Neuropathologica Communications, 2023)
Epithelial membrane protein 3 (EMP3) is an N-glycosylated tetraspanin with a putative trafficking function. It is highly expressed in isocitrate dehydrogenase-wild-type glioblastoma (IDH-wt GBM), and its high expression correlates with poor survival. However, the exact trafficking role of EMP3 and how it promotes oncogenic signaling in GBM remain unclear. Here, we show that EMP3 promotes EGFR/CDK2 signaling by regulating the trafficking and enhancing the stability of EGFR. BioID2-based proximity labeling revealed that EMP3 interacts with endocytic proteins involved in the vesicular transport of EGFR. EMP3 knockout (KO) enhances epidermal growth factor (EGF)-induced shuttling of EGFR into RAB7 + late endosomes, thereby promoting EGFR degradation. Increased EGFR degradation is rescued by the RAB7 negative regulator and novel EMP3 interactor TBC1D5. Phosphoproteomic and transcriptomic analyses further showed that EMP3 KO converges into the inhibition of the cyclin-dependent kinase CDK2 and the repression of EGFR-dependent and cell cycle transcriptional programs. Phenotypically, EMP3 KO cells exhibit reduced proliferation rates, blunted mitogenic response to EGF, and increased sensitivity to the pan-kinase inhibitor staurosporine and the EGFR inhibitor osimertinib. Furthermore, EGFR-dependent patient-derived glioblastoma stem cells display a transcriptomic signature consistent with reduced CDK2 activity, as well as increased susceptibility to CDK2 inhibition upon EMP3 knockdown. Lastly, using TCGA data, we showed that GBM tumors with high EMP3 expression have increased total and phosphorylated EGFR levels. Collectively, our findings demonstrate a novel EMP3-dependent mechanism by which EGFR/CDK2 activity is sustained in GBM. Consequently, EMP3’s stabilizing effect provides an additional layer of tumor cell resistance against targeted kinase inhibition.
Gesehen am 05.06.2024